Dom rodzinny jako miejsce komunikacji dziecka ze sprzężonymi zaburzeniami rozwoju – studium indywidualnego przypadku - Grzyb, Barbara; Kowalska, Gabriela (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The family homeis a place where all are acquired skills. Therefore, it is worth to be conducted workshops and training for parents, so that they will expand their interest in the field of science communication of the child with multiple developmental disorders.
Keywords: communication; development disorders; disabled child; family house; training